(3TaGA GdfaSs (3OQGSGJs - (3eQGO, jhSas; (3jMji, egfOs ((3GdbGgQIs (3JHGQc ddfTQ hGdJhRjYs, 2021)
(3Ydi nepqQ GdYUhpQ HMnK GdadGSaoI hYdeGoA GdfapS Yf eYfi GdnqSYGOI, hWQjbpI GdhUhpd EdjgG(B. (3haj gPG GdcJGpH jJfGhod GdeDpqdoa GdOcJhQ (S0(3jhSa eQGO(S1 (3CehkQG eKd JYQjpa GdnqSYGOI, hcja jJYnqQoa GdEfSGof Ydi chGepf fapSg djUnd HgG Edi Jdc GdSYGOpI GdefThOI(B. (3oKe ojHMoQ GdcJGoH aj ehVhYGmJ eKnd Ydpe GdUMpI GdYbdjpI hahGFpOg, hojfGboT GdoqfahnS GdeQjVnI hCfhGnYgG, hJCKjnQ GdHjFpI aj ofoThpA GdGfMQGaGpJ GdfaSjI, hJYQjna GdeQpV GdfaSpqj HhLmg YGe, hoWQnb GdYdGpL, neUMhHkI HCgpqe eOGQpS GdYdGpL GdnqfaSj, hYhGend GdTaGpA GdJj jLoH JhajoQgG ddeQjV(B. (3ojbpqOoe GdcJGoH HPdc oehLkRG hGakjG, dZjpQ GdeJNpqUUjf, HCSdhmH Sgmd hLnqPGHs
Keywords: (3GdCeQGV GdfaSjIs; (3GdEVWQGHGJ GdfaSjIs; (3GdUMI GdfaSjIs